Multiplication lattice modules - (:unkn) unknown (SHIRAZ UNIV, 2012)
Let M be a lattice module over the multiplicative lattice L. An L-module M is called a multiplication lattice module if for every element N is an element of M there exists an element a is an element of L such that N = a1(M). Our objective is to investigate properties of prime elements of multiplication lattice modules.
Keywords: Multiplicative lattice; lattice modules; maximal element; prime element; ELEMENTS